2017
DOI: 10.1016/j.anorl.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, pitfalls and risks of phytotherapy in clinical practice in otorhinolaryngology

Abstract: Scientific proof of the benefit of phytotherapy in otorhinolaryngology remains to be established but, given its widespread use and the reported data, knowledge of this form of treatment needs to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
0
15
0
2
Order By: Relevance
“…Although this review included more placebo‐controlled studies of east‐Asian TMs than earlier reviews, some studies may have been missed. Also, the focus was on east‐Asian TMs, so it does not include other categories of traditional medicine and phytotherapy . Each of these limitations should be considered when interpreting results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this review included more placebo‐controlled studies of east‐Asian TMs than earlier reviews, some studies may have been missed. Also, the focus was on east‐Asian TMs, so it does not include other categories of traditional medicine and phytotherapy . Each of these limitations should be considered when interpreting results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the focus was on east-Asian TMs, so it does not include other categories of traditional medicine and phytotherapy. 7 Each of these limitations should be considered when interpreting results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Polyphenol-rich herbal extract prepared from a rootof Pelargonium sidoides (EPs 7630) is traditionally used in South Africa for treatment of respiratory, gastrointestinal infections, and dysmenorrhea. 6,7 Sir Charles Henry Stevens introduced this herbal drug to England in 1897, and more than seven decades later, a special extract of Pelargonium sidoides root, EPs 7630 was made. 7 This substance has been reported as having antimicrobial and anti-inflammatory effects, and few controlled studies reported its safety and efficiency in reducing symptoms of uncomplicated upper respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicines have been used for centuries for the treatment of many disorders. In 2011, the World Health Organization estimated that 70-90% of population in developing countries and almost 20% in the United States used herbal drugs, whereas in Europe these percentages are estimated to 10-20% (8,9). The Myrtol® standardized, also known as GeloMyrtol® and GeloMyrtol® forte, with codifying number ELOM-080, is herbal medicine obtained through several steps of distillation of essential oils.…”
Section: Introductionmentioning
confidence: 99%